Mechanism of the impacts of older adults social participation on their health - Lin, Sheng Ai; Xu, Xueqing; Liu, Yutong; Ai, Bin (Frontiers in Public Health, 2024)
Purpose: Against the background of population aging challenges in China, focusing on health, security, and social participation as core elements of positive aging, this study aims to formulate strategies for promoting the health of the elderly and reveal the pathways and trends of social participation in promoting health.Method: The study analyzed 1015 randomly selected elderly individuals living at home in Beijing using household survey questionnaires. Drawing on group dynamics theory and structural equation modeling, the study proposed hypotheses regarding the relationships between social participation, group cohesion, and health status.Results: First, the triangular path model of social participation, group cohesion, and health status among the elderly was established. The direct path coefficient of social participation on health status was 0.15, that of social participation on group cohesion was 0.56, and that of group cohesion on health status was 0.32. The indirect path coefficient of social participation on health status through group cohesion was calculated at 0.56 × 0.32 = 0.18. Second, of the elderly age groups-younger, middle, and older-social participation's direct path effects on health status were present only in the older age group. Social participation's indirect path effects on health status through group cohesion were relatively high in all three groups, with a slight increase in the older age group.Conclusions: First, just the elderly's participation in social activities serves as a benign stimulus to physical and mental health. Additionally, group cohesion formed through interaction with others during social activities encourages self-improvement behaviors, indirectly promoting health. In fact, indirect pathways of health promotion through group cohesion are stronger than direct pathways, highlighting the importance of group cohesion during social participation. Second, participation in activities alone can provide only sufficient benign stimuli for the elderly aged 80 and above, with the direct path effect of social participation on health beginning to appear only with increasing age. With age, selectivity of interaction with others decreases, and dependence increases; social participation's indirect path effect on health through group cohesion continues to grow slightly.